2020
DOI: 10.1101/2020.08.20.258152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D mapping reveals a complex and transient interstitial matrix during murine renal development

Abstract: Background: The extracellular matrix (ECM) is a network of proteins and glycosaminoglycans that provides structural and biochemical cues to cells. In the kidney, the ECM is critical for nephrogenesis; however, the dynamics of ECM composition and how it relates to 3D structure during development is unknown. Methods: Using embryonic day (E)14.5, E18.5, postnatal day (P)3, and adult kidneys, we fractionated proteins based on differential solubilities, performed liquid chromatography tandem-mass spectrometry, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 92 publications
(142 reference statements)
0
8
0
Order By: Relevance
“…These included 83 BM proteins and the most abundant were those seen early (COL4A1, COL4A2, COL18A1, LAMB1, LAMC1) and later (LAMA5) in BM assembly (Figure 5-figure supplement 1C). We compared these findings to a proteomic dataset from the E18.5 mouse kidney (Lipp et al, 2021), and found considerable overlap, with a further 130 matrix protein identifications (Figure 5C), including key GBM components COL4A3, COL4A4, COL4A5 and COL4A6. We then compared the BM proteins from each organoid timepoint with E19 mouse kidneys (Figure 5D) and found the highest overlap (58.4%) between E19 and day 25 kidney organoids.…”
Section: Bms In Late-stage Organoids and Fetal Kidneys Are Highly Cor...mentioning
confidence: 97%
See 1 more Smart Citation
“…These included 83 BM proteins and the most abundant were those seen early (COL4A1, COL4A2, COL18A1, LAMB1, LAMC1) and later (LAMA5) in BM assembly (Figure 5-figure supplement 1C). We compared these findings to a proteomic dataset from the E18.5 mouse kidney (Lipp et al, 2021), and found considerable overlap, with a further 130 matrix protein identifications (Figure 5C), including key GBM components COL4A3, COL4A4, COL4A5 and COL4A6. We then compared the BM proteins from each organoid timepoint with E19 mouse kidneys (Figure 5D) and found the highest overlap (58.4%) between E19 and day 25 kidney organoids.…”
Section: Bms In Late-stage Organoids and Fetal Kidneys Are Highly Cor...mentioning
confidence: 97%
“…Most understanding about vertebrate BMs comes from immunolocalization and genetic knock-out studies (Abrahamson et al, 2013) and for composition, mass spectrometry (MS)-based proteomics has enabled global analysis (Naba et al, 2016;Randles et al, 2015). Proteomics also allows time course studies, which have provided insight into matrix dynamics during development and in disease progression (Hebert et al, 2020;Lipp et al, 2021;Naba et al, 2017). However, proteomics lacks the spatial context that is captured by localization studies including fluorescent tagging of endogenous proteins.…”
mentioning
confidence: 99%
“…These included 83 BM proteins and the most abundant were those seen early (COL4A1, COL4A2, COL18A1, LAMB1, LAMC1) and later (LAMA5) in BM assembly (Figure S5C). We compared these findings to a proteomic dataset from the E18.5 mouse kidney (Lipp et al, 2021), and found considerable overlap, with a further 130 matrix protein identifications (Figure 5C), including key GBM components COL4A3, COL4A4, COL4A5 and COL4A6. We then compared the BM proteins from each organoid timepoint with E19 mouse kidneys (Figure 5D) and found the highest overlap (58.4%) between E19 and day 25 kidney organoids.…”
Section: Bms In Late-stage Organoids and Fetal Kidneys Are Highly Correlatedmentioning
confidence: 97%
“…Most understanding about vertebrate BMs comes from immunolocalization and knock-out studies (Abrahamson et al, 2013) and for composition, mass spectrometry (MS)-based proteomics has enabled global analysis (Naba et al, 2016;Randles et al, 2015). Proteomics also allows time course studies, which have provided insight into matrix dynamics during development and in disease progression (Hebert et al, 2020;Lipp et al, 2021;Naba et al, 2017). However, proteomics lacks the spatial context that is captured by localization studies including fluorescent tagging of endogenous proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation